83 Volumetric assessment of tumour size changes in paediatric low grade gliomas: comparison with linear measurements and implications for determining response to therapy. (4th October 2017) - D'Arco, F; O'Hare, P; Dashti, F; Lassaletta, A; Loka, T; Bouffet, E; Tabori, U; Thust, S; Messalli, G; Hales, P; Laughlin, S
Abstract : Background: The aim of this study was to perform a comparison between bi-dimensional measurement of tumour diameter based on RANO and manual volumetric segmentation of paediatric low grade gliomas to determine response assessment. Methods: MR FLAIR images were used for assessment of tumour response with the exception of those patients in whom complete enhancement was present on the T1 post contrast sequences. Volumetric segmentations and calculation were undertaken using Osirix MD. Results: 70 patients aged 0.56 to 16.75 years were included this this single centre comparison of 2D and volumetric assessment of tumour response. For each patient 2 consecutive scans were assessed. 13 patients had a history of NF1 and 36 patients had a diagnosis of optic pathway glioma of which 20 were completely enhancing lesion. 14 (20%) of the 70 patients have discordant results between the assessment of tumour response using 2D and volumetric methods. All volumetric response assessments were in keeping with the subjective analysis of tumour. Of the 14 patients, 6 had stable disease (SD) on volumetric analysis and progressive disease (PD) on 2D assessment, 5 patients had SD on volumetric assessment and partial response on 2D analysis, 2 patients had PD on volumetric analysis and SD on 2D assessment, and 1 patient had partial response (PR) on volumetric analysis and SD on 2D analysis. Conclusion: Therapeutic response classification would change in a significant number of children performing a volumetric tumour assessment.